TRANSFORMASI DIGITAL UNTUK MASYARAKAT DESA: PELATIHAN SERVIS LAPTOP DAN MENGETIK 10 JARI DI DESA BONEMARAMBE – BUTON TENGAH - syahrullah, ichlas (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service program was conducted in Bonemarambe Village, Buton Tengah, aiming to promote digital transformation through laptop servicing and ten-finger typing training. The program was designed to enhance the community’s basic technological skills, particularly in hardware maintenance and efficient computer usage. The training results indicated significant improvements in participants' abilities to understand simple laptop repair techniques and increase typing speed using the ten-finger method. Challenges included limited facilities and lack of motivation among some participants. The strength of the program lies in the relevance of the material to the community’s growing reliance on technology, though limited resources hindered optimal outcomes. Future opportunities for development include introducing advanced technology training and collaborating with local institutions to broaden the scope of digital skills within the community. This initiative demonstrates that digital transformation in rural areas can begin with relevant and practical foundational training.